Challenges and Opportunities for Collegial Governance at Canadian Universities: Reflections on a Survey of Academic Senates - Pennock, Lea; Jones, Glen A.; Leclerc, Jeff M.; Li, Sharon X. (Canadian Journal of Higher Education, 2016)
Following the design of a similar study in 2000, the authors conducted a study of university senates (academic councils) to assess the current state of academic governance in Canada’s universities. An earlier paper presented and analyzed the data that were gathered about senate size, composition, structure, legislative authority and work, and about structural and governance changes to senates in the intervening decade. The current paper focuses on themes arising from responses to the open-ended questions, highlighting key findings. Significant findings relate to a sizeable discrepancy between senate members’ perceptions of the importance of effective academic oversight, and their success at achieving this. Suggested reforms include reviewing and improving senate performance; fostering a culture of trust and respect among and within governing bodies; clarifying spheres of authority and accountability; and promoting the importance of collegial governance and oversight within the institution.